Dinamika Sentimen dalam Mengelola Reputasi ONIC Esports pada MPL ID Season 13 - Rahmani, Nur Aisyah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Technological developments have had a significant impact on various aspects of human life, including the entertainment and sports sectors, resulting in a phenomenon known as esports. Mobile Legends: Bang Bang is one of the dominant online multiplayer games in Indonesia and the Mobile Legends Professional League (MPL) is the main platform for professional players to build a reputation. ONIC Esports, one of Indonesia's esports teams, has a strong reputation for winning various competitions, including being runner-up in the MLBB M5 World Championship in 2023. However, maintaining a positive reputation in a dynamic environment like esports requires media monitoring. This research uses a descriptive qualitative method to explore the dynamics of sentiment towards ONIC Esports in MPL ID Season 13. Through a netnography approach, researchers use the Brand24 social media analysis tool to collect positive and negative sentiment data from various online platforms. By focusing on the first to third weeks of MPL ID Season 13, this research aims to understand the impact of news and sentiment on ONIC Esports' reputation.